Eksistensi tokoh anak dan tokoh kakek sebagai pengemban pesan profetik dalam cerpen-cerpen Kuntowijoyo - Efendi, Anwar (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
The purpose of this study is to describe the prophetic message portrayed through the characters within Kuntowijoyo’s fiction. The focus of the study is limited to the existence of the child and the grandfather and also their relation in conveying the prophetic message. The sources of the data for this study are Kuntowijoyo’s novel along with his fiction collections. Thus, the data are gathered through document collection. Those data are analyzed using an interactive analysis method, which results in simultaneous data collection and analysis. The findings of the study show that: (1) the grandfather character is portrayed as the symbol of the afterlife; (2) the child character symbolizes life itself; (3) the relationship between both characters—the child and the grandfather—can be concluded as a binary opposition. The child, who marks the beginning of life, becomes the emphasis of the grandfather’s symbol as the end of life.